2012
DOI: 10.1021/la300412u
|View full text |Cite
|
Sign up to set email alerts
|

Foam Consolidation and Drainage

Abstract: A theoretical model of foam as a consolidating continuum is proposed. The general model is applied to foam in a gravity settler. It is predicted that liquid drainage from foam in a gravity settler begins with a slow drainage stage. Next, a stage with faster drainage occurs where the drainage rate doubles compared to the initial stage. The experiments conducted within the framework of this work confirmed the theoretical predictions and allowed measurements of foam characteristics. Foams of three different conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Bending deformations of the elastic envelopes displace water from the foam space, as in the case of conventional foam drainage (Jun et al . ). A conventional polyhedral liquid foam is stabilized by a disjoining pressure in the thin lamellae of the foam (Kornev et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Bending deformations of the elastic envelopes displace water from the foam space, as in the case of conventional foam drainage (Jun et al . ). A conventional polyhedral liquid foam is stabilized by a disjoining pressure in the thin lamellae of the foam (Kornev et al .…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the hydrate envelope can be easily deformed when bubbles contact each other. Bending deformations of the elastic envelopes displace water from the foam space, as in the case of conventional foam drainage (Jun et al 2012). A conventional polyhedral liquid foam is stabilized by a disjoining pressure in the thin lamellae of the foam (Kornev et al 1999); a polyhedral solid hydrate foam is stabilized by a thin hydrate layer on the boundary of the gas phase.…”
Section: Second Controlling Factor Of Bubble Transformationmentioning
confidence: 99%
“…In the case of foams built up by Newtonian liquids, equations of drainage were deduced using the combination of the liquid momentum and mass balance equations [4][5][6][7][8]. The drainage equations in the case of Newtonian liquids have been solved numerically and/or analytically in different prototype situations including free drainage [4][5][6][7][8][9], where liquid drains out of a foam due to the influence of gravity and capillarity; wetting of a dry foam [10,11], where a dry foam is in contact with a liquid at its base; forced drainage [8,9,[12][13][14], where liquid is added to the top of foam column producing a traveling wave; and pulsed drainage [8,[15][16][17], where a small volume of liquid is injected to the top of a foam and left to evolve. A new type of these situations is the case of foam drainage placed on a porous substrate [18,19], where foam is deposited on a porous substrate and the presence of unsaturated pores inside the porous substrate results in an imbibition of liquid from the foam into the unsaturated pores.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of both phases (and the components in the phases) control the dynamics of foam behaviour and eventually affect foam longevity. While many studies have shown the impact of the components of the aqueous phase on foam stability [1,[4][5][6][7][8][9], the effect of type and composition of the gaseous phase has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…4 Calculated using (1). 5 Perry's chemical engineering handbook, chapter 2 [48]. 6 Calculated by (7) of Norman et al, 1954 [49].…”
Section: Introductionmentioning
confidence: 99%